Komodifikasi Tubuh Perempuan dalam Iklan Yoghurt Bio Berbahasa Prancis: Analisis Wacana Multimodal - Aufinda, Calyaputri Rafa; Andriani, Merry (Faculty of Humanities, Diponegoro University, 2025)
The goal of this research is to determine how women’s bodies are commodified through analysing the use of visual and verbal elements in the French Bio yoghurt advertisement. The analysis was conducted using Gunther Kress and Theo van Leeuwen’s multimodal theory as well as Firouzeh Nahavandi’s theory of body commodification to examine how women’s bodies become commodities in the media context. Research data in the form of a video clip of advertisements was taken from the official website of Institut national de l’audiovisuel. This research uses qualitative descriptive methods. The results indicate two forms of commodication of women’s bodies in Bio yoghurt advertisements, consisting of commodification of women bodies through sensuality and through youthful body. Women’s bodies as an important part of the marketing strategy for Bio yoghurt products. The combination of visual elements, such as the gestures and actions performed by the actors in the advertisement, eye contact, camera focus on certain parts, shooting techniques, lighting direction, colours, and verbal elements, such as narration, shows that women’s bodies are commodified to create appeal so that the audience is interested in watching the advertisement, which then leads them to buy and consume Bio yoghurt products. This finding confirms that women’s bodies are used as capitalist values, that sensual, happy, young and healthy bodies are bodies that can be shaped and maintained through product consumption.